A macroeconomic model for the evaluation of labor market reforms - Tom Krebs; Martin Scheffel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
We develop a tractable macroeconomic model with employment risk and labor market search in order evaluate the effects of labor market reform on unemployment, growth, and welfare. The model has a large number of risk-averse households who can invest in risk-free physical capital and risky human capital. Unemployed households receive unemployment benefits and decide how much search effort to exert. We present a theoretical characterization result that facilitates the computation of equilibria substantially. We calibrate the model to German data and use the calibrated model economy to simulate the macroeconomic effects of the German labor market reforms of 2005 and 2006 (Hartz Reforms). We find that the 2005-reform had large employment effects: the equilibrium unemployment rate has been reduced by approximately 1.1 percentage points from 7.5 to 6.4 percent. Moreover, the drop in unemployment has led to substantial output gains. Finally, employed and short-term unemployed households experienced significant welfare gains, whereas the long-term unemployed have lost in welfare terms. The effects of the 2006-reform are qualitatively similar, but quantitatively much smaller. We also show that the social welfare maximizing replacement rate is lower than the current (post-reform) replacement rate in Germany. However, implementing the optimal unemployment benefit system generates only small welfare gains.
Keywords: E24; E60; J64; J65; 330; dynamic general equilibrium; heterogenous agents; human capital; labor market search; unemployment insurance; German labor market reform; Arbeitsmarktpolitik; Reform; Ökonometrisches Makromodell; Dynamisches Gleichgewicht; Theorie; Hartz-Reform; Wirkungsanalyse; Wohlfahrtseffekt; Schätzung; Deutschland